Diagrama de fases magnéticas e transição de fase quântica em ligas de Cr-Ti - Varella, André Luiz Soares (Universidade Federal de São Carlos, 2009)
In this work we present the results of characterization of Cr-Ti alloys with small quantities of Ti. The samples were prepared in a melting arc furnace, using hight purity Cr and Ti. The magnetic phase diagram was determined from critical temperatures obtained by eletrical resistivity and DC magnetic susceptibility measurements, delimiting the boundaries between the transverse and longitudinal SDW (Spin Density Wave) and paramagnetic phases. We have observed that the Band Rigid Model is valid only for concentrations below 1.5%Ti. Above this concentration, a possible structural phase transition explain the disappearance of antiferromagnetic phase. From the observation of anomalies in resistivity ratio, magnetic susceptibilty and Hall effect measurements at low temperature, we have concluded that the system exhibits a quantum critical point in 1.2%Ti.
Keywords: Propriedades magnéticas; Antiferromagnetismo; Cromo; Ondas de densidade de Spin; Transição de fase quântica; CIENCIAS EXATAS E DA TERRA::FISICA